Emerging Religious Movements And Their Implications In African History And Heritage - Emmanuel Osewe Akubor (European Scientific Journal, ESJ, 2016)
Africa has often been referred to as the Home of Civilization. This reference is based on the fact that most of the continent evidences how man has, over time, interacted meaningful with his environment to produce all that he needs to make history. Archaeological remains in Egypt have shed light on this development as far as Africa is concern. Other remains found particularly in central Eastern Africa have been widely recognized such that the area is now widely accepted as the origin of humans and the Hominidae clade (great apes). This is evidenced by the discovery of the earliest hominids and their ancestors, as well as later ones that have been dated to around seven million years ago. These later ones include Sahelanthropus tchadensis, Australopithecus africanus, A. afarensis, Homo erectus, H. habilis, and H. ergaster, with the earliest Homo sapiens (modern human) found in Ethiopia dating far back to circa 200,000 years ago. Now, this rich historical heritage is being threatened by the emergence of some religious movements in Africa. The reason for this is that these religions see the preservation of these relics as idolatry and unacceptable. Data obtained from primary and secondary sources were deployed to carry out the study, and the study was carried out with an analytical and narrative historical method. Findings indicate that while the European world continue to beg for the preservation of these artifacts and in some cases preserve these artifacts and relics in their museums, the emerging groups continue to target these historical artifacts for destruction. This paper argues that this trend is unhealthy for the development of history and preservation of the continent’s heritage. Furthermore, it asserts that once this wanton destruction is not checked, there is a high possibility that in the nearest future, nothing would be left to study in African history.